Reforming the WTO's subsidy rules. A new opportunity to tackle the global distortions of China's state capitalism - Jürgen Matthes; Samina Sultan (Institut der deutschen Wirtschaft (IW), 2023)
The African Group proposes to reform the WTO's subsidy rules for industrial goods. Even if this demand for more policy space entails some problems, the EU should view this as an opportunity. By combining the African Group's proposal with new rules against tradedistorting industrial subsidies by major global players, the EU can start a new initiative to tackle global economic distortions emanating particularly from nonmarket economies. While this initiative is no panacea, it offers various attractive advantages.
Keywords: 330